Strategic Initiatives to Enhance Employee Well-Being in Startup Organizations - Afiifah, Jauharotul; Putra Pratama, Andika (Riviera Publishing, 2025)
In the dynamics of environmental startup organizations, employee well-being plays a critical role in sustaining performance and organizational growth. This study aims to explore strategic initiatives that can enhance employee well-being. Drawing upon the MARS Model of individual behavior and performance, the research examines how motivation, ability, role perception, and situational factors influence well-being outcomes. In addition, the PERMA Model consisting of Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment is integrated to provide a holistic understanding of psychological well-being in the workplace. A mixed-method approach was employed, combining quantitative surveys with qualitative interviews among employees from selected startups. The findings reveal that flexible work arrangements, open communication culture, and recognition systems are key drivers of well-being. Moreover, a strong alignment between individual goals and organizational values significantly correlates with higher job satisfaction and performance. This study provides practical recommendations for startup leaders to design human resource strategies that prioritize employee well-being as a foundation for sustainable success.